Mayaro Virus as the cause of Acute Febrile Illness in the Colombian Amazon Basin - Perez-Restrepo, Laura S.; Ciuoderis, Karl; Usuga, Jaime; Moreno, Isabel; Vargas, Vanessa; Arévalo-Arbelaez, Angela J.; Berg, Michael G.; Cloherty, Gavin A.; Hernández-Ortiz, Juan Pablo; Osorio, Jorge E. (Frontiers in Microbiology, 2024)
Mayaro Fever (MF) is a tropical disease caused by the Mayaro virus (MAYV), with outbreaks documented in Latin America. A hospital-based fever surveillance in Leticia, Colombian Amazon, collected sera from 1460 patients aged 5 to 89 between December 2020 and April 2023. Dengue and malaria were the main diagnoses (19.4% and 5.8%, respectively), leaving 71.4% of cases unidentified after testing. Metagenomic sequencing and real-time RT-qPCR testing identified MAYV in two patients (25-year-old male and an 80-year-old female) exhibiting typical symptoms, of mayaro fever including rash, joint pain, and fever. Phylogenetics analysis of these two viruses revealed a close relationship to Peruvian strains within the MAYV D genotype. This study presents the first near fulllength genomes of MAYV in Colombia, highlighting the need for further seroprevalence studies and enhanced surveillance to understand and control the spread of the virus in the region.